PENGARUH PERSEPSI MANFAAT, PERSEPSI KEMUDAHAN DAN KEPERCAYAAN TERHADAP MINAT MENGGUNAKAN UANGELEKTRONIK BRIZZI BRI - Cahaya, Yohanes Ferry; Randa, Putera Muhammad (Jurnal Ilmiah Manajemen SURYA PASCA SCIENTIA, 2025)
This study aims to examine and analyze the influence of perceived usefulness, perceivedease of use, and trust on the intention to use BRIZZI BRI electronic money. The researchemploys a quantitative method with purposive sampling, involving a total sample of 100respondents. Data analysis was conducted using multiple linear regression tests, t-tests,and determination coefficient tests, supported by IBM SPSS Statistics Version 25. Theindependent variables in this study are perceived usefulness, perceived ease of use, andtrust, while the dependent variable is the intention to use BRIZZI BRI electronic money.The findings indicate that perceived usefulness, perceived ease of use,and trustsignificantly shape user interest in using BRIZZI BRI. Specifically, perceived usefulnesshas a positive and significant influence on the intention to use BRIZZI BRI electronicmoney, indicating its substantial role in driving user interest. Conversely, perceived easeof use exhibits a negative influence, suggesting it does not affect the intention to use theproduct. Meanwhile, trust has a positive and significant impact, highlighting its critical rolein enhancing user interest in using BRIZZIBRI electronic money.